Determining The Acceptance ,Forgiveness, Gratitude And Spirituality As Predictirs Of Resilience Among Staff In Rehabilitation Centres - Sallina Mansor (Universiti Sains Islam Malaysia, 2024)
Resilience among staff working in the Malaysian government’s drug treatment and rehabilitation centres (DTRC) is of paramount importance because this quality helps to ensure that the staffs are able to carry out their tasks and responsibilities with the greatest professionalism, competence and effectiveness. This study examines their resilience and the role of acceptance, forgiveness, gratitude and spirituality in enhancing the staff’s resilience while working in these centres. In this study, the level of acceptance, forgiveness, gratitude, spirituality and resilience are determined. A comparison of these factors of acceptance, forgiveness, gratitude, spirituality and resilience is made based on the demographic characteristics (gender, length of services, category of DTRC and job grade scale). The mediating role of spirituality on the relationship of acceptance, forgiveness and gratitude with resilience was also determined. This descriptive and quantitative study undertakes to observe 380 respondents recruited from the DTRC staff throughout the country of Malaysia. The main research instrument used in this study is a questionnaire which comprises several scales encompassing the Connor-Davidson Resilience Scale, the Acceptance and Action Questionnaire, the Heartland Forgiveness Scale, the Gratitude Questionnaire, and the Daily Spiritual Experience Scale. The IBM SPSS version 23.0 and Amos 23.0 were used to run the descriptive and inferential statistics. Results show that the perception of the respondents on the values of acceptance, gratitude and spirituality is high but the perception of the respondents on forgiveness is moderate while for resilience it was moderately high. The values of acceptance, forgiveness, gratitude, spirituality and resilience were not significantly different between the male and female respondents. Based on the length of services and the category of DTRC, results also show significant difference in forgiveness but not significant on acceptance, gratitude, spirituality and resilience. A comparison based on job grade scale shows that there is no significant difference in gratitude and spirituality but there is a significant difference in acceptance and forgiveness whereby a higher and significant mean difference was seen in officers when compared to assistant officers. In addition, acceptance, forgiveness, gratitude and spirituality were also noted to be significant predictors of resilience. Forgiveness was observed to be giving the greatest effect followed by spirituality and acceptance and finally, gratitude. This study shows that the values of acceptance, forgiveness and gratitude can explain 34.8 percent of the variance noted in spirituality whereas the values of acceptance, forgiveness, gratitude and spirituality can explain 82.6 percent of the variance in resilience. Spirituality is a significant mediator for the relationship between acceptance, forgiveness and gratitude with resilience. This study also shows that the values of acceptance, forgiveness, gratitude and spirituality are strong and important predictors of resilience. Therefore, staffs who exhibit these virtues are able to become more resilient and so more capable of coping with the stressful situations at the DTRCs.